How to Obtain an Aldicarb Application Permit for Florida Cotton or Peanut - Zane J. Grabau; Ethan Carter; Libbie Johnson; Jay Ferrell; Dale Dubberly; Tamara James (EDIS)
This publication is intended to guide growers through the process of applying for a free permit to use aldicarb, an insecticide/nematicide subject to particular restrictions because of its highly toxic nature and concerns about groundwater contamination when it is improperly applied. Aldicarb is currently labeled only for cotton and peanut in Florida. It is a restricted-use pesticide; thus applicators must have a current and valid private or commercial Florida pesticide applicator’s license with a row crop category designation and must obtain an aldicarb permit from Florida’s Department of Agriculture and Consumer Services before applying this product in Florida. This publication provides a guide to the permit application process for aldicarb.